ANALYSIS OF THE DIFFICULTY INDEX OF SIXTY PSYCHOLOGY ITEMS IN THE FINAL EXAMS OF SECONDARY SCHOOL STUDIES IN THE DRC: CASE OF THE GOMA FINALISTS. - MATSORO MITONDO Amédée (IJRDO- Journal of Educational Research, 2025)
This article analyzes 60 items of the psychology sub-branch taken from 8 years Session of the State Examinations in the Democratic Republic of Congo. We proceeded to the analysis of the items by calculating for each item, the index of difficulties. After analysis, we found that the indexes of difficulties are 0.15 to 0. 80 subsequently these indexes were ranked from the highest index (easiest item to the lowest index item) to the most difficult. The formula used is that of GULLIKSEN